2021
DOI: 10.3389/fpsyt.2021.602293
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Ruminative Thinking in Individuals With Gender Dysphoria

Abstract: This study aimed to examine psychosocial factors and medical history as well as symptoms of depression, anxiety, and stress associated with ruminative thinking in transgender people with gender dysphoria (GD) before undergoing gender affirmation surgery (GAS). This study evaluated 189 participants with GD (111 trans women and 78 trans men) from a specialized service for GAS in southern Brazil. Semi-structured interviews were conducted, and participants were asked to complete self-report questionnaires. We reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…While not all trans individuals will seek out hormones, access to and use of hormones can be lifechanging among those who do, particularly those with gender dysphoria. Individuals with gender dysphoria experience distress related to differences between their sex assigned at birth and gender identity (Ashley, 2021) and may experience episodes of distress, ruminative thinking, anxiety, and depression (Bouman et al, 2017;Chodzen et al, 2019;Klemmer et al, 2021;Silva et al, 2021). As gender-affirming hormones are highly effective in developing secondary sex characteristics and are less costly and more accessible than gender-affirming surgeries, hormones are most often the first or only form of gender-affirming care trans patients will seek out (Restar et al, 2019;White Hughto & Reisner, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While not all trans individuals will seek out hormones, access to and use of hormones can be lifechanging among those who do, particularly those with gender dysphoria. Individuals with gender dysphoria experience distress related to differences between their sex assigned at birth and gender identity (Ashley, 2021) and may experience episodes of distress, ruminative thinking, anxiety, and depression (Bouman et al, 2017;Chodzen et al, 2019;Klemmer et al, 2021;Silva et al, 2021). As gender-affirming hormones are highly effective in developing secondary sex characteristics and are less costly and more accessible than gender-affirming surgeries, hormones are most often the first or only form of gender-affirming care trans patients will seek out (Restar et al, 2019;White Hughto & Reisner, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Rumination is another general factor that may underlie the mental health impacts of minority stressors. Rumination is associated with higher levels of suicidal ideation, depression, and anxiety in transgender individuals (Silva et al, 2021). Furthermore, in their cross-sectional study, Timmins et al (2017) found that distal and proximal stressors were related to distress for transgender people and that rumination partially accounted for these associations.…”
Section: Minority Stressors and Mental Healthmentioning
confidence: 99%
“…A total of 17 380 records were identified from the search, with 286 studies 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ...…”
Section: Resultsmentioning
confidence: 99%